Impact of pregnant mothers’ previous COVID-19 infection and vaccination on newborns’ serological profiling - Masry, Alaa; Bayoumi, Mohammad A. A.; Chandra, Prem; Abukhadijah, Hana J.; Olukade, Tawa; Abdelhady, Ismail; Thazhe, Sudheer; Paramban, Ratheesh; Sudarsanan, Anoop; Abraham, Jeat; Abugubba, Mohammed; Al-Matar, Yasser; et al. (Frontiers in Immunology, 2025)
BackgroundPregnant women and newborns are at-risk groups for coronavirus disease 2019 (COVID-19). There is a paucity of evidence to prove the degree of perinatal passive immunity transfer from COVID-19-vaccinated or COVID-19-infected mothers to their newborns.MethodsWe prospectively investigated the vaccination and infection status of 70 women included in the study, as well as the serological characteristics of 72 newborns, to investigate the in utero transmission of maternal antibodies against COVID-19 to newborn infants between 2021 and 2022.ResultsA total of 70 pregnant mothers were included in the study after providing signed informed consent. After delivery, cord blood samples were collected from all 72 newborns included in the study. The COVID-19-vaccinated group had significantly higher (p < 0.001) values of both antibodies (NTAb*3.31 and S-RBD*1.15) in the cord blood across both the COVID-19-positive and COVID-19-negative groups. The antibody titres were the lowest in mothers who were not vaccinated and the highest in those who received three vaccination doses (p < 0.001). Multivariate linear regression analysis was performed using dependent variables NTAb*3.31 and S-RBD*1.15 antibodies and independent predictor variables nationality, infant’s gender, COVID-19 vaccination status, and COVID-19 test status; the multivariate linear regression analysis results indicated that vaccination against COVID-19 remained a potential significant (p < 0.0001) predictor for both NTAb*3.31 and S-RBD*1.15 antibodies after adjusting other potential predictor variables.ConclusionsIn our study, we found significantly higher titres of NTAb*3.31 and S-RBD*1.15 antibodies in newborns’ cord blood whose mothers had previous COVID-19 infection or received COVID-19 vaccination; however, these titres were higher in the case of vaccination than previous infection. The more doses of vaccine received, the higher the antibody levels in newborns’ cord blood. This indicates transplacental immunity transmission from mothers to their newborns after previous COVID-19 vaccination or infection.